High-Efficiency Thermal Tuning of a Long-Period Fiber Grating Using a Liquid Crystal Layer - Czapla, Aleksandra; Bock, Wojtek J; Woliński, Tomasz R (Photonics Letters of Poland, 2009)
A high-efficiency thermal tuning filter based on a long-period fiber grating (LPFG) with a liquid crystal cladding layer is presented. The filter exhibits two different temperature sensitivities which depend on the temperature range of operation: for the temperatures from 23°C to 38°C, the thermal sensitivity is 0.279 nm/°C and for 41°C to 52°C, it is 0.929 nm/°C. These values are increased by more than one order of magnitude over the value for LPFGs without a liquid crystal layer whose thermal tuning efficiency is 0.056 nm/°C. The results show that the idea of integrating the LPFGs and the liquid crystals (LCs) into a single component opens up a wide range of new possibilities for developing novel high-efficiency thermal tuning devices with a fast response speed.